1981
DOI: 10.1111/j.1365-2214.1981.tb00851.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of gender identity in the autistic child

Abstract: The Michigan Gender Identity Test (MGIT) was administered to 30 autistic children to determine whether autistic children could demonstrate a sense of gender identity. The results of the MGIT were correlated with other developmental indices obtained from the Alpern-Boll Developmental Profile. From this sample of autistics, a significant relationship was found between gender identity and mental age, chronological age, communication skills, physical skills, social skills, self-help skills and academic (cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Despite the increase in research on GID in children in recent decades, publications on gender identity development and gender‐related problems in autistic children are very limited. To my knowledge, Abelson's (1981) study is the first study that evaluates the development of gender identity in children with autism. He reported a significant relationship between gender identity and mental age, chronological age, communication skills, physical skills, self‐help skills and academic skills.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increase in research on GID in children in recent decades, publications on gender identity development and gender‐related problems in autistic children are very limited. To my knowledge, Abelson's (1981) study is the first study that evaluates the development of gender identity in children with autism. He reported a significant relationship between gender identity and mental age, chronological age, communication skills, physical skills, self‐help skills and academic skills.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of all the studies can be found in Tables 1 and 2. Abelson [28] published the first study into the development of gender identity in children with autism. Gender identity was assessed through the Michigan Gender Identity Test (MGIT) [38] with 30 children who had a clinical diagnosis of Autism.…”
Section: Publications On Children and Adolescentsmentioning
confidence: 99%
“…Out of the 19 articles, eight were case reports [13,21,22,23,24,25,26,27] and four were cohort studies. The first cohort study explored the development of gender identity in children with Autism [28], the second established the co-occurrence of ASD and Gender Dysphoria [12], the third attempting to establish predictive factors for autism spectrum traits [29], and the fourth reviewed the overrepresentation of adolescent developmental problems in minors with Gender Dysphoria [30]. Six studies considered within this systematic review were case control studies, two of which employed the AQ to compare autism spectrum traits within a sample of patients with Gender Dysphoria and a control group [16,31].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There are also the group differences in sex recognition to consider. Experiments by Abelson (1981) and Hobson (1987) have suggested an abnormality in autistic children's capacity to classify bodily characteristics according to sex. Although Weeks & Hobson (1987) reported that autistic children were not different from matched non-autistic retarded children in their propensity to sort photographs of people according to sex, hair length rather than gender might have provided the critical feature for the observed pattern of sorting.…”
mentioning
confidence: 99%